A Summary of N, P, and K Research with Tomato in Florida - George Hochmuth; Ed Hanlon (EDIS)
More than 60 years’ worth of tomato fertilization research has been conducted in Florida. During this time, many changes have occurred in tomato production practices, including changes in cultivars and the introduction of new cultural systems, such as polyethylene mulch and drip irrigation. The research reported here covers tomato production with polyethylene mulch. Tomato crop and fertilizer management recommendations, such as plant and row spacing, have changed over time following new developments in research. This revised 38-page fact sheet summarizes tomato fertilization research leading to current University of Florida recommendations and summarizes needs for additional research. Written by George Hochmuth and Ed Hanlon and published by the UF Department of Soil and Water Science, August 2011. (UF/IFAS Photo by Tyler Jones)